The effect of establishment method and shade zones within solar arrays on pasture production in agrivoltaics production system - Dazaea, Azad; Higgins, Chad W.; Rosati, Adolfo; Graham, Maggie; Ates, Serkan (Frontiers in Sustainable Food Systems, 2025)
Integrating livestock grazing with photovoltaic (PV) systems offers a promising strategy to enhance both agricultural and energy outputs from the same land. However, limited information is available on how field preparation methods and microclimatic conditions affect pasture establishment and productivity. This study evaluated the effects of three field preparation methods and intra-array shading on pasture germination, establishment, and herbage yield in an agrivoltaic system. Treatments included: (i) tillage followed by plastic cover (TP), (ii) plastic cover only (P), and (iii) herbicide application only (H), all applied prior to sowing. A diverse pasture mixture, comprising perennial ryegrass (Lolium perenne L.), orchardgrass (Dactylis glomerata L.), white clover (Trifolium repens L.), birdsfoot trefoil (Lotus corniculatus L.), chicory (Cichorium intybus L.), and plantain (Plantago lanceolata L.) was sown in between ground-mounted PV panels in spring 2020. Pastures were harvested periodically over two growing seasons from four 1 m-wide zones (A to D) within the alleys between arrays, with shading intensity decreasing from zone A (south side, under the panels) to zone D (north side of the alley). Photosynthetic photon flux density (PPFD) was monitored using calibrated photodiodes. TP resulted in the highest seedling establishment (782 plants/m2, p < 0.01), followed by P (681 plants/m2), and H (457 plants/m2). However, herbage production did not differ significantly among establishment methods in either 2020/21 (p = 0.10) or 2021/22 (p = 0.17). Herbage production was substantially lower in the most shaded zone (A) compared to the other zones (p < 0.01), while zones B, C, and D, despite varying light availability produced similar herbage yields, with zone D underperforming relative to zones B and C despite higher light input. These findings suggest that while field preparation influences seedling establishment, it has limited long-term impact on biomass production. In contrast, heavy shading in zone A substantially restricts productivity, whereas light availability in the remaining zones does not appear to be the primary limiting factor for herbage yield. This insight can inform design and management strategies to maximize agricultural productivity in agrivoltaic systems.